2017
DOI: 10.1016/j.mcn.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-specific demethylase-1 (LSD1) depletion disrupts monogenic and monoallelic odorant receptor (OR) expression in an olfactory neuronal cell line

Abstract: Function of the mammalian olfactory system depends on specialized olfactory sensory neurons (OSNs) that each express only one allele ("monoallelic") of one odorant receptor (OR) gene ("monogenic"). The lysine-specific demethylase-1 (LSD1) protein removes activating H3K4 or silencing H3K9 methylation marks in a variety of developmental contexts, and is thought to be important for proper OR regulation. Most of the focus in the field has been on a potential "activating" function for LSD1; e.g., in the demethylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…ND, No detectable expression of either NQO1 or NCAM2. ͓1͔, ISH performed in the current study; ͓2͔, ISH reported by Serizawa et al (2000); ͓3͔, ISH reported by ; ͓4͔, ISH reported by Grosmaitre et al (2006); ͓5͔, ISH reported Tsuboi et al (2006); ͓6͔, ISH reported by Zhao et al (2013); ͓7͔, ISH reported by Kaluza et al (2004). OR locations identified by association with OR family members are indicated by ͓family͔.…”
Section: Expression Of Multiple Ors In Omp(؉) Osnsmentioning
confidence: 59%
See 1 more Smart Citation
“…ND, No detectable expression of either NQO1 or NCAM2. ͓1͔, ISH performed in the current study; ͓2͔, ISH reported by Serizawa et al (2000); ͓3͔, ISH reported by ; ͓4͔, ISH reported by Grosmaitre et al (2006); ͓5͔, ISH reported Tsuboi et al (2006); ͓6͔, ISH reported by Zhao et al (2013); ͓7͔, ISH reported by Kaluza et al (2004). OR locations identified by association with OR family members are indicated by ͓family͔.…”
Section: Expression Of Multiple Ors In Omp(؉) Osnsmentioning
confidence: 59%
“…The localization in normal OE of the amplified OR was determined by ISH ( Fig. 6A) and, when available, compared to published patterns of OR expression (Serizawa et al, 2000;Kaluza et al, 2004;Grosmaitre et al, 2006;Tsuboi et al, 2006;Zhao et al, 2013). We validated both the purity of cells transplanted as well as the sensitivity of our FACS isolation after transplant (Fig.…”
Section: Adaptation To the Ventral Oe As Measured By Ocam Expression mentioning
confidence: 84%
“…We have previously shown that only one OR allele (“monoallelic”) of one OR gene (“monogenic”) is expressed at detectable levels in individual OP6 cells, and that many OR genes are expressed in entire OP6 cultures at various passages [ 30 , 31 , 33 ]. Given that OP6 cultures are clonally derived [ 29 ], these observations indicate that OR re-selection has occurred–if OR choice was stable, we would predict that OP6 cultures would be ~homogeneous with respect to OR expression.…”
Section: Resultsmentioning
confidence: 99%
“…For several years, we and others have used the OP6 cell line as a model for studying OR gene regulation. Based on previous work [ 30 , 31 , 33 ], individual OP6 cells appear to express only one dominant OR allele (monogenic, monoallelic), like mature OSNs in vivo . Therefore, the OP6 cell line provides an opportunity to investigate mechanisms of OR gene selection in a developmentally ~homogeneous (i.e., clonal) cell population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation